Morphological diversity of fish size and otolith dimension of the protandrous hermaphroditic fish Eleutheronema tetradactylum from Pattani Bay, Thailand - TEUKU HARIS IQBAL; SUKREE HAJISAMAE; SOFIYUDIN MAAE; ILHAM ZULFAHMI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Iqbal TH, Hajisamae S, Maae S, Zulfahmi I. 2025. Morphological diversity of fish size and otolith dimension of the protandrous hermaphroditic fish Eleutheronema tetradactylum from Pattani Bay, Thailand. Biodiversitas 26: 1807-1815. This study examines the morphological diversity of otolith dimensions across different sexes and size classes of Eleutheronema tetradactylum from Pattani Bay, Thailand. A total of 303 specimens (166 males, 137 females) were collected using monofilament gillnets from May to December 2021. Measurements of Standard Length (SL) and Body Weight (BW), Otolith Length (OL), Otolith Height (OH), and Otolith Weight (OW) were taken to the nearest size of 0.01 mm and weight of 0.001 g. Ordinary Least Squares (OLS) regression, Student's t-test, and One-way Analysis of Variance (ANOVA) were applied to estimate relationships and significant differences between sexes and size classes. The highest correlation was observed between SL and BW with OL in males (R2: 0.95). Significant differences were found in otolith parameters between sexes and size classes; females exhibited significantly larger otoliths than males, and the larger size of fish was also associated with significantly larger otoliths than those of smaller fish (P<0.01). These findings highlight the correlation between fish size and otolith dimensions, demonstrating otolith analysis as a useful tool for growth estimation and stock differentiation of E. tetradactylum populations.